An alternative model of measuring human capital - Kozioł, Wojciech (Management and Administration Journal, 2023)
The aim of the article is to present an alternative model of human capital and its possible applications in economics and management. This model builds on the general model of capital using the traditional rules in force in the accounting measurement. The combination of these accounting rules with the discovery of constant economic growth potential (which is the discount factor model)allows for the accurate measurement of individual capital and human capital. A description of the human capital model has been extended to compare it with classic models of human capital, including the concept of the human capital of Becker and Schultz. The article contains the presentation of the principles of pay for human capital. These principles arise from the nature of capital and human capital. The presented method of measurement and principles of proper pay for human capital are used in economics and management. In particular, this allows solving a number of important issues of pay, such as the minimum wage, adequate wage inequalities in the economy, wages in the public sector, and may also provide the basis for remunerating companies. They provide an alternative to the dominant economic literature paramount role in shaping the labour market wages.